A Review on the Structure-function Relationship of Class II α-Mannsoidases - Shashidhara K.S.; Mahmed Juned Contractor; Kanavi, M.S.P.; Prakash Koler.; Prashanth Kumar H.P. (Archives of Current Research International, 2025)
Of fundamental importance to every function an enzyme or a protein performs is its three-dimensional structure. The structure plays a crucial, though often subtle, role in catalysis. The conformational changes in enzymes are often small, and even these small changes could be significant. Glycosylation modifications of proteins and glycan hydrolysis are critical for protein function in biological processes. Aberrations in glycosylation enzymes are linked to lysosomal storage disorders (LSD), immune interactions, congenital disorders, and tumour progression. Alpha-Mannosidases Class 2B is a lysosomal hydrolase. Dysfunction of this has been implicated as a causative factor in mannosidosis, a lysosomal storage disorder characterized by cognitive impairment, hearing loss, and immune system and skeletal anomalies. Despite decades of research, its role in pathogenic infections, autoimmune conditions, cancers, and neurodegenerative pathologies is highly ambiguous. Although many Class II α-mannosidases have been reported from various sources but not many of them have been characterized structurally. Through the combined efforts of various types of spectroscopies and protein crystallography, structure-function relationship studies in some Class II α-mannosidases from various sources have been carried out, and the same has been reported. The structure of Class II α-mannosidases from different sources has revealed the involvement of various types of folding of the protein, the presence of metal ions such as Zn+ in the active site, and their role in substrate specificity and catalytic mechanism is reviewed here.